pH and proton sensor GPR65 determine susceptibility to atopic dermatitis - Xie, L; McKenzie, CI; Qu, X; Mu, Y; Wang, Q; Bing, N; Naidoo, K; Alam, MJ; Yu, D; Gong, F; Ang, C; Robert, R; et al. (The American Association of Immunologists, 2021)
pH sensing by GPR65 regulates various inflammatory conditions, but its role in skin remains unknown. In this study, we performed a phenome-wide association study and report that the T allele of GPR65-intronic single-nucleotide polymorphism rs8005161, which reduces GPR65 signaling, showed a significant association with atopic dermatitis, in addition to inflammatory bowel diseases and asthma, as previously reported. Consistent with this genetic association in humans, we show that deficiency of GPR65 in mice resulted in markedly exacerbated disease in the MC903 experimental model of atopic dermatitis. Deficiency of GPR65 also increased neutrophil migration in vitro. Moreover, GPR65 deficiency in mice resulted in higher expression of the inflammatory cytokine TNF-α by T cells. In humans, CD4+ T cells from rs8005161 heterozygous individuals expressed higher levels of TNF-α after PMA/ionomycin stimulation, particularly under pH 6 conditions. pH sensing by GPR65 appears to be important for regulating the pathogenesis of atopic dermatitis.